(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-210-219 The process of formation of children’s journalism in Kalmykia dates back to a difficult and contradictory period of the 1930s. The Kalmyk children’s press traces roots back to the year 1934 when the first pioneer newspaper "Lenina achnr" (”Lenin’s grandchildren”) was organised. In genre terms, the newspaper was very diverse, as in addition to the usual information ‒ articles, sketches, etc., it included poems, stories, plays, fairy tales of not only Russian and Kalmyk authors, but also Ossetian, Karakalpak, Dagestan and other writers. The diversity of the newspaper’s content was complemented by such folklore genres as riddles, proverbs, charades, etc. Genre features and topical content of the publication in question form its typological model, which represents one of the most important factors in the individualization of children’s media of that time. a number of issues related to the involvement of the young generation in the socio-political life of society and their importance in the educational activities of that time are being researched. Functionally designated purpose, problem-thematic diversity of the first children’s newspaper and the current state of national children’s periodicals are brought to light. Key words: national press, children’s journalism of Kalmykia, pioneer publications, newspaper «Lenina achnr»